ANALISIS HUBUNGAN KEAHLIAN AUDIT DAN PENGUNGKAPAN KEY AUDIT MATTERS TERHADAP KUALITAS AUDIT - Azizah, Farah Nur; Mayangsari, Sekar (JURNAL ILMIAH EDUNOMIKA, 2024)
This research analyzes the impact of auditor expertise and disclosure of Key Audit Matters (KAMs) on audit quality. Auditor expertise refers to the auditor's ability to accurately identify and evaluate complex accounting issues, which is an important factor in improving audit quality. Additionally, KAM disclosures increase the transparency of the audit process, address information asymmetry, and increase reliability by clearly providing key audit matters and response plans to stakeholders. This research concludes that high auditor expertise and transparent KAM disclosure complement each other to improve audit quality. Through this, auditors and stakeholders can obtain more reliable financial information, which ultimately contributes to improving the company's financial health and transparency. The sample in this research is external auditors who have worked for 1-5 years and more than 5 years at KAP. The data collected is primary. The type of data is quantitative data using a questionnaire formula. The sample collection technique is purposive sampling technique. The analytical tool used is SPSS version 25. Tests related to validity and reliability tests, double linear analysis, determination coefficient tests, multicolinearity tests, heterocedase tests, autocorrelation tests, hypothesis tests. The results of this research are that audit expertise has a significant effect on audit quality and audit matter disclosure has a significant effect on audit quality.